Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/access.2020.3003521
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PSOS-CGSA Method for State Estimation in Unbalanced DG-Integrated Distribution Systems

Abstract: This paper proposes a novel optimization method, namely, hybrid PSOS-CGSA for state estimation in three-phase unbalanced DG-integrated distribution systems. The distribution system state estimation (DSSE) is formulated as a nonlinear optimization problem with constraints where loads and DG outputs are considered as the control variables, while real-time measurements are treated as dependent variables. The proposed DSSE model estimates the loads and DG outputs at each bus by minimizing the difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…As more information is used in the estimation framework, the uncertainty in the estimation can be decreased. To further increase the estimation performance, future research directions include: systematically study the features related to the dynamics of sulfur concentrate grade; embed more information related to the dynamics of sulfur concentrate grade in the estimation framework, e.g., trend information [36]; increase the optimization performance of the estimation algorithm [37]; combine deep learning, reinforcement learning and control theory with the estimation framework [38][39][40][41]; design robust moving horizon estimation to increase the stability of estimation performance.…”
Section: Discussionmentioning
confidence: 99%
“…As more information is used in the estimation framework, the uncertainty in the estimation can be decreased. To further increase the estimation performance, future research directions include: systematically study the features related to the dynamics of sulfur concentrate grade; embed more information related to the dynamics of sulfur concentrate grade in the estimation framework, e.g., trend information [36]; increase the optimization performance of the estimation algorithm [37]; combine deep learning, reinforcement learning and control theory with the estimation framework [38][39][40][41]; design robust moving horizon estimation to increase the stability of estimation performance.…”
Section: Discussionmentioning
confidence: 99%
“…PSO has been widely applied to optimize the performance of electrical power systems including economic dispatch [237][238][239], optimal power flow [240][241][242], state estimation [243], power system controllers [244,245], unit commitment [246] and capacitor placement [247]. A detailed and thorough survey on the applications of PSO in electrical power systems is provided in [248].…”
Section: Electrical Power Systemsmentioning
confidence: 99%
“…The proposed technique can achieve lower power loss when compared with the individual PSO and ABC algorithms; nevertheless, its performance is not compared with high-performance PSO variants as well as with other well-known meta-heuristic algorithms such as GWO and whale optimization algorithm (WOA). The work in [243] hybridized PSO with gravitational search algorithm to solve the problem of state estimation in distribution systems. Results have shown that the proposed hybrid scheme is more accurate and reliable than the standard PSO algorithm and the original GSA approach.…”
Section: Electrical Power Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The equality constraints for the ORPD problem are typical nonlinear power flow equations for three-phase unbalanced DNs [22,23].…”
Section: Equality Constraintsmentioning
confidence: 99%